Friends Help Couple Mark 40th Mr. & Mrs. Ortiz (Raton, New Mexico Raton Range, 1992)
Newspaper Article on the 40th Anniversary of Mr. & Mrs. Daniel Ortiz.
Master list item #: 14
File location is in the Raton File Cabinet
Keywords: Ortiz, Daniel; Ortiz, (Mrs); Casias, Pete; Morrow, Barbara; Vigil, Molly; Nolan, Alfanso; Nolan, (Mrs); Nolan, Junior; Nolan, (Mrs); Nolan, Paul; Nolan, (Mrs); Armijo, Sam; Armijo, (Mrs); Padilla, Phil; Padilla, (Mrs); Cruz, Willie; Cruz, (Mrs); Cruz, Henry; Quintana, Bob; Quintana, (Mrs); Tish; Louise; Cordova, Tinnie; Cordova, (Mrs); Montoya, Larry; Montoya, (Mrs); Cordova, Ernest; Roybal, Paul; Roybal, (Mrs); Acevedo, Joe; Acevedo, (Mrs); Trujillo, Eddie; Trujillo, (Mrs); Mares, Mabel; Salas, Toby; Salas, (Mrs); Cordova, John; Cordova, (Mrs); Cordova, Misty; Mendez, Danny; Mendez, (Mrs); Martinez, Louis; Martinez, (Mrs); Sanchez, Tom; Sanchez, (Mrs); Nolan, Fernando; Vigil, Juanita; Tafoya, Faustina; Sanchez, Mary Lou; Biography; Local History; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Miami, New Mexico; Trinidad, Colorado; Pueblo, Colorado; Cimarron, New Mexico